New intervention strategy for postoperative fatigue syndrome in elderly patients with colorectal cancer: a clinical hypothesis study based on vagus nerve stimulation - Yin, Xuefeng; Qiao, Shuang; Zhang, Ling; Li, Zhonghua; Zhang, Qin; Shen, Yu; Fan, Keyu; Liu, Mingxia; Wang, Dongxu; Cao, Ya; Zhang, Yuxuan; Qian, Lu; et al. (Frontiers in Medicine, 2025)
Postoperative fatigue syndrome (POFS) comprises symptoms including fatigue, insomnia, inattention, depression, tension, and anxiety following surgery. These manifestations encompass exhaustion, weakness, malaise, and emotional disturbances, impacting hospital stay duration, quality of life, rehabilitation progress, and work performance. While the etiology of POFS remains complex, recent evidence suggests that external stimuli may induce pro-inflammatory cytokine release, leading to fatigue. Surgical procedures trigger an inflammatory reaction that stimulates the nervous system, generating fatigue symptoms. Both animal and human studies demonstrate that vagus nerve stimulation (VNS) can reduce pro-inflammatory cytokine production by activating the cholinergic anti-inflammatory pathway (CAP). Considering the pivotal role of inflammation in the development of POFS and the vagus nerve's capacity to modulate inflammatory responses, we hypothesize that transcutaneous auricular vagus nerve stimulation (taVNS) holds significant potential for alleviating POFS in elderly patients undergoing colorectal cancer surgery. In this paper, we propose a hypothetical scheme to validate this hypothesis through the application of taVNS in future clinical studies.